Cover Feature: Direct Conversion of Polypropylene into Liquid Hydrocarbons on Carbon‐Supported Platinum Catalysts (ChemSusChem 23/2021). Issue 23 (17th November 2021) - Jaydev, Shibashish D.; Martín, Antonio J.; Pérez‐Ramírez, Javier
Abstract : The Cover Feature shows a landscape reflecting the pressing problem of plastic waste generation where a resolute humanoid emerges, symbolizing the potential of chemical recycling. The golden color embodies the high value of products that this strategy can yield, such as the liquid hydrocarbons obtained from the hydrogenolysis of polypropylene as described in the manuscript. Carbon‐supported Pt catalysts enable this outcome, for which activity and selectivity are tunable via Pt particle size and surface oxygen content of carbon, respectively. More information can be found in the Full Paper by S. D. Jaydev et al .